Trust in Organizational and Workplace Deviant Behavior The Moderating Effect of Locus of Control - Abdul Rahman Abdul Rahim; Aizzat Mohd. Nasurdin (Gadjah Mada International Journal of Business, 2008)
This study seeks to investigate the moderating role of locus of control (LOC) in the relationship between trust in organization (TiO) and workplace deviant behavior (WDB). Three forms of deviant behavior are identified: interpersonal deviance, production deviance, and property deviance. The regression analyses carried out on a sample of 355 employees show mixed results. Trust in organization (TiO) demonstrates a negative relationship with production deviance and property deviance. In contrast, trust in organization (TiO) is positively related to interpersonal deviance. Furthermore, locus of control (LOC) is found to moderate the relationship between trust in organization (TiO) and deviant behaviors. Implications, limitations, and suggestions for future research are discussed.